Partycypacja polityczna i wyborcza diaspory w kraju pochodzenia: Przegląd literatury przedmiotu - Magdalena Lesińska (University of Warsaw, Centre of Migration Research (CMR), 2015)
– The text examines the main issues emerging in the scientific literature concerning the participation of diaspora in the political sphere of the country of origin, it also summarizes the conclusions from existing research and studies. Subsequent chapters are devoted to the main concepts and approaches currently developing within the diaspora studies and related to its political activities, as well as the complex relations between diaspora and the country of origin (including main actors, forms and institutions involved). The review of literature and research focuses in particular on the phenomenon of external voting - participation of citizens residing abroad in national elections in the country of origin and the main factors determining the process of political and electoral participation of diaspora.
Keywords: 330; diaspora; political participation; voting rights; literature review; emigration; Polish diaspora; political discourse; political programs and parties